Mitigating water depletion through wastewater management law in Indonesia’s textile sector: Evaluating compliance and alignment with national environmental standards - Wara Angi Josse Charmario; Al Mukarramah Nurul Habaib; Maskun Maskun (BIO Web of Conferences)
This study argues that the compliance of mandatory wastewater management regulations in Indonesia’s textile industry sector is low, which consequently amplifies environmental pollution, water scarcity due to depletion and the changing climate. This study addresses two research question(s): How does Indonesian law regulate wastewater management in the textile industry sector? Based upon the current practice, what challenges hinder its implementation? This study utilizes normative legal research methodology by analyzing Indonesian legal instruments and relevant case laws. It highlights the significant challenges arising from the unwillingness of various stakeholders to enforce environmental regulations, including government entities holding licensing instrument authority and companies non-compliance. In conclusion, the current framework for defining wastewater contamination thresholds requires substantial improvement by adopting more stringent, ambitious, climate conscious standards. It is recommended to: 1) incentivize companies demonstrating interest in environmental compliance but lacking necessary financial resources; 2) reward companies that have become exemplary leaders in wastewater management; and 3) encourage a reevaluation of existing legal frameworks regarding wastewater quality standards, with a view to adopting ambitious and measurable environmental standards.